Impact of learning and forgetting factors on organizational learning effectiveness with the moderation of information system and mobile technology - Ali, Jamshid (2020)
In this research project, the focus was on evaluating the impact of organizational learning and forgetting factors using information system and mobile technology as the moderator for organizational learning effectiveness. Due to the shift from paper based working environment to paper-less environment and under the directions of Commission of Higher Education of Pakistan (HEC), the learning organizations like universities faced several problems and loosed organizational knowledge. Many universities were facing organizational learning and preservation problems while changing from paper-based environment to the paper-less environment. This research explored the role of information system and mobile technology as a moderator with organizational learning and forgetting factors for the organizational learning effectiveness. Data was collected from 392 faculty members of the 160 public and private sector universities registered with Higher Education Commission (HEC). Cross-sectional survey, quantitative in nature, based on adopted questionnaire was designed to achieve the objectives of the study using stratified sampling at first phase and convenient sampling technique at the second phase. The findings showed that information system and mobile technology have significant role in organizational learning effectiveness. Information system was assessed with organizational learning and forgetting factors and it was proven as a supportive tool with greater impact for organizational learning effectiveness together with cognitive factors, behavioral factors and social factors with the information system as a moderator. Similarly, taking information technology as a moderator with organizational forgetting factors also resulted in a similar significant impact. Furthermore, taking mobile technology as a moderator with organizational cognitive, behavioral and social factors produced values that showed significant impact of the mobile technology on organizational learning effectiveness. The findings also recommend and suggest the deployment of information system to capture, store, and disseminate organizational knowledge for learning and development effectiveness. Information systems play their role in both learning and forgetting for their capacities to acquire and forget certain models, methods and techniques. Similarly, mobile technology was tested with the organizational learning factors as a moderator and the results showed that mobile technology has significant effect on organizational learning effectiveness. The study also contributed to the organizational theory, socio-cognitive theory and institutional theory by recognizing the work of information system and mobile technology. This research further recommends the idea to explore the organizational processes and outcomes under ambiguity. Similarly, leadership role can be explored for organizational learning and forgetting at different organizational level and also the use of block chain technology for organizational learning effectiveness.